Hypomagnesemia in Type II Diabetes - Rehab El-Megrabi; Maryouma Aghil; Mariam Elahjal; Muna Elkouha; Ghada Amir; Hala Altuwati (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and aims. Magnesium (Mg) is an important cofactor in a number of important enzymatic reaction and appears to play an important role in glucose metabolism and insulin homeostasis. There is a link between mg deficiency and type 2 diabetes. The present study was conducted to estimate serum mg levels in Type 2 Diabetes Mellitus (DM2) patients and to correlate these levels with pathogenesis. Methods. A total of 70 samples were collected from males and females aged from 20 to 80 years to compare the level of mg in each of them, and the samples were divided into two groups, group1 (n=40) for patients with type II diabetes and group2 (n=30) for healthy people. People with other chronic diseases such as hypertension, heart disease and thyroid disease were excluded. The percentage of mg was determined in the (Dimension RXL Max). Results. About 49 females out of 70 that represent 70% of our community whereas 21 males that represent 30 %. 30 of participants (42.9%) were non-diabetic (Health) while the other 40 participants (57.1%) were diabetic (patients). Although there was a negative correlation between the two variables, this difference was not significant (p =.238). Conclusion. Our research demonstrated an inverse relationship between magnesium levels and HbA1c in individuals with DM2. Our study adds to the existing evidence for this negative correlation, elucidating the intricate connections that give rise to this relationship. To obtain more precise results, future investigations conducted on a broader scale are imperative.